The Eastern Mediterranean and the making of global radicalism, 1860-1914 - Khuri-Makdisi, Ilham (California world history library, 2010)
Establishes the existence of a special radical trajectory spanning four continents and linking Beirut, Cairo, and Alexandria between 1860 and 1914. This book shows that socialist and anarchist ideas were regularly discussed, disseminated, and reworked among intellectuals, workers, dramatists, Egyptians, Ottoman Syrians, and others in these cities.